2013
DOI: 10.1007/s00018-013-1297-1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and environmental epigenetic programming of the endocrine pancreas: consequences for type 2 diabetes

Abstract: The development of the endocrine pancreas is controlled by a hierarchical network of transcriptional regulators. It is increasingly evident that this requires a tightly interconnected epigenetic "programme" to drive endocrine cell differentiation and maintain islet function. Epigenetic regulators such as DNA and histone-modifying enzymes are now known to contribute to determination of pancreatic cell lineage, maintenance of cellular differentiation states, and normal functioning of adult pancreatic endocrine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 175 publications
0
29
0
2
Order By: Relevance
“…Pancreatic islet mass is reduced and ␤-cell proliferation diminished in CL mice. Similarly, multiple animal models, including maternal protein restriction, caloric restriction, and intrauterine placental ligation models, have identified common metabolic phenotypes in offspring and have identified alterations in insulin sensitivity and the pancreatic ␤-cell (26,30,36,53,56,61). ␤-Cell mass and proliferation were also reduced in GHR-deficient mice (37), and the number of large islets was reduced in Ames dwarf mice (55).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic islet mass is reduced and ␤-cell proliferation diminished in CL mice. Similarly, multiple animal models, including maternal protein restriction, caloric restriction, and intrauterine placental ligation models, have identified common metabolic phenotypes in offspring and have identified alterations in insulin sensitivity and the pancreatic ␤-cell (26,30,36,53,56,61). ␤-Cell mass and proliferation were also reduced in GHR-deficient mice (37), and the number of large islets was reduced in Ames dwarf mice (55).…”
Section: Discussionmentioning
confidence: 99%
“…Altered pancreatic beta cell function represents a central mechanism associated with developmental programming of T2DM [29,30]. Early life conditions including both under and overnutrition are associated with insulin resistance in key organs controlling glucose homeostasis, including liver, muscle and adipose tissue in adult life placing considerable pressure on the beta cell.…”
Section: The Endocrine Pancreasmentioning
confidence: 99%
“…To identify the effects of gain of mTORC1 function during the developmental period on the susceptibility to diabetes induced by maternal protein restriction, we transiently induced mTORC1 signaling from embryonic day 14.5 to birth identified common metabolic phenotypes in offspring and have identified the pancreatic β cell as particularly sensitive to nutrients very early in life (3,29,30). In these experiments, we used engineered animal models with spatial and temporal regulation capabilities to dissect the molecular mechanisms responsible for developmental programming by low protein.…”
Section: Ripcre Tsc2mentioning
confidence: 99%
“…Genetic studies have demonstrated that known variants account for less than 10% of the estimated overall genetic contribution to T2D predisposition, suggesting that additional unidentified factors contribute to susceptibility of this disease (1, 2). The fetal nutrient environment has been proposed as another component that might modify the risk for developing diabetes later in life (3). There is increasing evidence that alterations in fetal nutrients not only affect fetal/infant growth but also promote a "thrifty phenotype" that increases the subsequent risk of metabolic syndrome, obesity, and T2D (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation